THE CORRELATION BETWEEN PSYCHOSOCIAL RISK FACTORS AND WORK PERFORMANCE IN MANUFACTURING INDUSTRY - Nuruzzakiyah MI; Ezrin Hani S; Hanida AA (Malaysian Journal of Public Health Medicine, 2020)
Nature of psychosocial risk as to the unseen hazards in the working population, potentially exposing the workers towards the adverse effect of mental health. Compromising the well- being of mental health could lead to deterioration of work performance. The objective of this study is to analyze the constructed measure of psychosocial risk factors and work performance of manufacturing workers using statistical analysis. Then, the constructed measure is used to find the correlations between the two factors. A set of the questionnaire is administered to 258 manufacturing workers. The questionnaires were adapted and adopted from Copenhagen Psychosocial Questionnaire (COPSOQ III), NIOSH Generic Job Stress Questionnaire, and Individual Work Performance Questionnaire (IWPQ 1.0) and the instrument were found to be reliable (Cronbach Alpha value = 0.7 ). After conducting Exploratory Factor Analysis by using Principal Component Analysis, the construct validity to conduct data collection in the manufacturing industry is tested. Using eight factors understudy that already extracted using factor analysis, it is found that there are significant psychosocial risk factors present in the manufacturing industry. As for the association between psychosocial and work performance, it is found that there is a significant association between psychosocial risk factors and work performance. This study is essential to explore the presence of psychosocial risk factors that underlies in the manufacturing industry, which might affect worker performance and well-being. For future research, it is recommended so that this study can be replicated to other manufacturing industry or different types of industries to see the robustness of the developed instruments. At the same time, the issue of psychosocial risk factors and workers’ performance also can be identified, and the mitigation can be planned.